Promoting Infant Mental Health Through Evidence-Informed Interventions to Support Infant Feeding and the Transition to Parenthood: A Clinical Practice Example. Issue 2 (June 2020) - Buchan, Judy L.; Bennett, Claudine T.
Infant mental health is influenced by many factors including the successful transition to parenthood and the feeding relationship with caregivers. Region of Peel – Public Health in Ontario, Canada promotes infant mental health through interventions that encourage cue-based feeding and responsive infant care that helps individual families meet their infant feeding goals and build a foundation of responsive parenting. Interventions have been developed to meet the needs of a large, ethnically diverse population. The use of a biodevelopmental framework identifying nutrition and the environment of relationships as important foundations of health provided key areas of focus for Nurturing the Next Generation, a public health strategic priority. Research evidence, literature syntheses, local research, and data informed the interventions. The promotion of a positive nursing practice environment supports the public health nurses who deliver these interventions. This framework of effective public health practice contributes to long-term health outcomes, including the promotion of mental health for infants, their families, and the population.